First Steps 123 - Lesley Clark (UK Ladybird Books Ltd., 1997)
Aiming to teach two to four-year-olds basic numeracy, this book combines photographs and illustrations to aid learning. It features large, illustrated numbers, which are also given in words and shown on a counting bead string. There are photographs of objects and toys, and activity puzzle pages.